The evolutive mind debate - VV.AA, VV.AA. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
IGNACIO SILVA: I am not sure if you are familiar with the last book of Massimo Piattelli-Palmarini what Darwin got wrong, and there are a couple of points that interestinglyclearly converge with some of Teilhard’s positions or suggestions. [...].